Pengaruh Penggunaan Standar Pelaporan GRI, NPM, Size, DER, dan Kepemilikan Manajerial terhadap Pengungkapan Akuntansi Sumber Daya Manusia (Studi pada Perusahaan Pertambangan dan Manufaktur di Bei Tahun 2016-2019) - Romy Chandra Gita; Gede Adi Yuniarta (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
The purpose of this study was to empirically prove the effect of GRI guidelines, NPM, size, DER, and managerial ownership structure toward disclosure of human resource accounting. This research was a quantitative study using secondary data obtained from the company's annual report. The population of this study were all mining and manufacture sector companies listed on the Indonesia Stock Exchange during the 2016-2019 period. The sampling technique in this study was purposive sampling. The samples that met the purposive sampling criteria in this study were 44 companies. The data analysis technique used was multiple linear regression analysis using SPSS version 24 software. The results showed that partially GRI guidelines, NPM, size, and DER had a positive effect toward disclosure of human resource accounting, while managerial ownership structure negatively affected disclosure of  human resource accounting.